Environmental Impact of Beef Cattle Production Systems - Nicolas DiLorenzo; G. Cliff Lamb; Jose Dubeux; John Arthington; Joao Vendramini; Phillip Lancaster (EDIS)
This 6-page fact sheet discusses beef demand in the context of a growing population, beef production’s greenhouse gases and their effect on the environment, the great advantage of ruminants, generating accurate greenhouse gas emissions estimates, greenhouse gas emissions by economic sector, and mitigation strategies. Written by Nicolas DiLorenzo, G. Cliff Lamb, Jose Dubeux, John Arthington, Joao Vendramini, and Phillip Lancaster and published by the UF/IFAS Department of Animal Sciences, November 2014. (UF/IFAS Photo by Thomas Wright)